Urban growth management and territorial governance approaches: A master plans conformance analysis - Menzori, Ivan Damasco; Sousa, Isabel Cristina Nunes de [UNESP]; Gonçalves, Luciana Márcia (Elsevier, 2021)
Urban sprawl is related, among other factors, to local planning policies that aim to drive economic growth through spatial planning but fail to regulate urban expansion. Even land use plans originally designed to restrict urban sprawl appear to be ineffective when approached by local authorities. Withal, little attention has been given into analysing local master plans implementations and their relation with territorial governance. In this paper, we focus on the role of territorial governance arrangements in master plans implementation practices. Also, we explore the spatial outcomes of urban growth in a medium-sized Brazilian city, conformance wise to its Master Plans, under different administrations from contrasting political parties. The purpose is to identify discrepancies in urban growth spatial outcomes, according to territorial governance, quantitatively assessing whether the observed growth complied with zoning strategies or comprised nonconforming development. It is arguable that governance capacity affects the spatial distribution of urban growth and, consequently, the regulation of urban sprawl. The results show disparate patterns of urban growth corresponding to different administrations, even under the same plan implementation, suggesting that the spatial outcomes could have been shaped either by the enforcement or the abstention of planning regulations, characterizing contrasting approaches on territorial governance.
Keywords: Brazil; Global South; Plan implementation; Urban containment policies; Urban expansion